2017
DOI: 10.3906/biy-1606-28
|View full text |Cite
|
Sign up to set email alerts
|

Induction of haploid plants in citrus through gamma-irradiated pollen and ascertainment of ovule age for maximum recovery of haploid plantlets

Abstract: The present investigation was carried out for the induction of haploid plants in Citrus grandis through in situ parthenogenesis by pollination with gamma-irradiated pollen of C. limetta and C. sinensis, treated with 50, 100, 200, 300, and 400 Gy gamma ray doses followed by in vitro ovule culture. Ovule culture at 50 days after pollination (DAP) was found optimum for the maximum recovery of in vitro-raised plantlets as compared to 35 and 20 DAP. At 50 DAP, irrespective of the pollen parent, plantlet regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Lower irradiation doses between 25 to 50 Gy were found to be the best for haploid induction in squash (Kurtar et al 2002) (Gürsöz et al 1991) and cucumber (Sauton 1989;Lot et al 1999). Doses of 300 to 400 Gy were optimum for mandarin (Froelicher et al 2007) and citrus (Kundu et al 2017). Relatively higher dose of 1500 Gy was effective for haploid induction in kiwifruit (Chalak and Legave 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower irradiation doses between 25 to 50 Gy were found to be the best for haploid induction in squash (Kurtar et al 2002) (Gürsöz et al 1991) and cucumber (Sauton 1989;Lot et al 1999). Doses of 300 to 400 Gy were optimum for mandarin (Froelicher et al 2007) and citrus (Kundu et al 2017). Relatively higher dose of 1500 Gy was effective for haploid induction in kiwifruit (Chalak and Legave 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Higher fruit set ratio was observed in bottle gourd at lower irradiation doses, however, no haploid plantlets were obtained in six tested bottle gourd genotypes pollinated with irradiated pollen at lower irradiation doses up to 100 Gy (Table1, 2). A reasonable explanation for this tendency is that lower irradiation doses partially inactivate the pollen grains, which turns to their normal germination and fertilization of the egg cells, and formation of diploid embryos(Cuny 1992;Kundu et al 2017;Hooghvorst et al 2020). Besides, our results showed that not all six tested bottle gourd genotypes could regenerate haploid plantlets irrespective of irradiation doses.…”
mentioning
confidence: 99%
“…ex Tanaka). Since then, haploid plants have been produced by anther culture [17][18][19][20], interploid hybridization [21][22][23] and the pollination of irradiated pollen [24][25][26][27][28]. However, these haploids were very weak and grew more slowly than the original diploid plants.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests an alternative method to develop to produce haploids in this recalcitrant genotype. Irradiated pollen technique (UV, gamma rays and X-rays) is currently used successfully to induce in situ haploid plants (Kundu et al 2017). Irradiated pollens are genetically inert, physiologically active and can easily be germinated on the stigma, but are not able to fertilize the egg cell and the polar nuclei.…”
mentioning
confidence: 99%